2023
DOI: 10.3390/gels9080664
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Hydrogels for Water Purification Applications

Mariana Chelu,
Adina Magdalena Musuc,
Monica Popa
et al.

Abstract: Chitosan-based hydrogels have gained significant attention for their potential applications in water treatment and purification due to their remarkable properties such as bioavailability, biocompatibility, biodegradability, environmental friendliness, high pollutants adsorption capacity, and water adsorption capacity. This article comprehensively reviews recent advances in chitosan-based hydrogel materials for water purification applications. The synthesis methods, structural properties, and water purification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 231 publications
0
5
0
Order By: Relevance
“…Its hydrophilic and 3D structure determines permeabil-ity for bioactive substances [22], which enables it to retain significant amounts of water and biological fluids. Chitosan homopolymers maintain the integrity of their network and do not dissolve in water at neutral pH, but they can be dissolved in acidic conditions due to the protonation of free amino groups [40].…”
Section: Structure Of Chitosan and The Process Of Obtaining Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its hydrophilic and 3D structure determines permeabil-ity for bioactive substances [22], which enables it to retain significant amounts of water and biological fluids. Chitosan homopolymers maintain the integrity of their network and do not dissolve in water at neutral pH, but they can be dissolved in acidic conditions due to the protonation of free amino groups [40].…”
Section: Structure Of Chitosan and The Process Of Obtaining Hydrogelsmentioning
confidence: 99%
“…Since hydrogels have properties similar to liquids, molecules may be readily diffused, absorbed, and released [6]. Adding chitosan into the hydrogel structure makes it more hydrophilic, allowing it to swell and expand in the presence of liquid [40,52]. In addition to chitosan concentration, examples of key agents influencing the physicochemical properties of these hydrogels are cross-linkers (e.g., genipine, glutaraldehyde) and hydroxy acids (e.g., mandelic acid, lactobionic acid), which affect morphology, swelling ability, viscosity, mechanical strength, or cytotoxicity [53][54][55][56].…”
Section: Advantages Of Chitosan-based Hydrogelsmentioning
confidence: 99%
“…Grafting and cross-linking of pristine chitin afforded the obtaining of hydrogels with enhanced adsorption properties compared to the starting polysaccharide. Literature from the last decade showed that the introduction of different fillers (GO, r-GO tannic acid) in chitin-based gels have been utilized successfully in dye removal processes due to the enhanced adsorption properties of obtained composites [65,66] (Table 2).…”
Section: Chitosan and Chitin-based Hydrogelsmentioning
confidence: 99%
“…Currently, a variety of modern products have been commercially launched for wound care, including foams, films, hydrocolloids, hydrogels, and hydrofibers. Hydrogels are ideal wound dressings due to their exceptional biological properties [68][69][70][71]. Dressings based on hydrogels are considered advanced successful systems and particularly useful tools in biomedical practice.…”
Section: Biomaterials-based Hydrogels In Skin Tissue Engineering Surg...mentioning
confidence: 99%